QUR'ANIC RECEPTION THROUGH NUZULUL QUR'AN COMMEMORATION TRADITION AS A SYMBOL OF COMMUNITY UNIFYING IDENTITY - Shinta Nurani; Luthfi Maulana; Anidah Robani (Universitas Muhammadiyah Surakarta, 2022)
This article discusses the community's receptivity to the Qur'an based on ethnographic studies in the Commemoration of Nuzul al-Qur'an which was held at the Khoirunnisa' Mosque and Majlis Taklim, Gondang Village, Wonopringgo District, Pekalongan Regency. The people in the area are very heterogeneous and consist of five ideologies namely Nahdlatul Ulama, Muhammadiyah, Rifa'iyah, and Nationalist. The commemoration of Nuzul al-Qur'an in the last 10 days of the month of Ramadan begins with the khataman of the Qur'an, general recitation, then the recitation of four important chapters in the Qur'an, namely Surat Yasin, Surat al-Rahman, Surat al-Waqi'ah, and Surat al-Mulk. The four surahs are believed by the community to be able to maintain security, order, integrity, unity, unity and the community to get ease of life in various ways. This series of commemoration of Nuzul al-Qur'an has been carried out from generation to generation with great enthusiasm and reverence by the community. Even though the heterogeneity of society is very high, the Commemoration of Nuzul al-Qur'an is able to become a symbol of the unifying identity of Muslim communities that bridges the diversity of societal ideologies.